Headline Construction In @Jakarta.Keras Instagram Account: Systemic Functional Linguistics Approach - Cahya, Jodi; Lubis, Donal Fernado (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study analyzed how the Instagram account @jakarta.keras constructed its news headlines through a system of transitivity within the framework of Systemic Functional Linguistics (SFL) proposed by Halliday and Matthiessen (2014). Using a qualitative descriptive method, fifty news headlines were collected and analyzed to identify six types of processes: material, mental, relational, verbal, behavioral, and existential. The results show that material processes dominate (50%) with an emphasis on concrete actions and real events, followed by relational (18.48%), mental (17.39%), verbal (11.96%), and existential (2.17%) processes, with no behavioral processes found. This dominance indicates that @jakarta.keras tends to frame social reality through action-oriented narratives that highlight specific events and figures. Mental and relational processes contribute to the formation of emotional engagement and social judgment, while verbal and existential processes strengthen credibility and the discovery of new things. Overall, this study found that language in digital news headlines not only functions as a means of conveying information, but also as a strategic tool in constructing meaning and ideology.